(untitled) (Journal of Universal Science Research, 2025)
In the rapidly evolving landscape of global education, traditional classroom-based teaching is no longer sufficient to address the diverse, dynamic needs of modern learners. The emergence of blended learning—a pedagogical model that strategically combines face-to-face instruction with online and technology-driven components—has revolutionized the way knowledge is delivered, received, and processed. This model not only bridges the gap between conventional and digital teaching methods but also provides a more flexible, student-centered, and interactive learning experience